One Leader, One Party, One Truth: Public Television Under the Rule of the Populist Right in Poland in the Pre-Election Period in 2019 - Żuk, Piotr (Javnost-The Public, 2020)
The article analyses the way in which public television operates under the rule of right-wing populists in Poland. The author examines the content of the main mews programmes in the period preceding the parliamentary election in 2019 and defends the thesis that state-owned media in Poland have become a propaganda tool of the ruling party. The propaganda of the populist Right in the analysed programmes was based on two threads: the promise of social assistance from the populist authorities and nationalist, homophobic and exclusionary ideology. From this perspective, the government's opponents were portrayed not as competitors in the political dispute, but as ‘enemies of the nation’ subordinated to ‘foreign forces’. The political opposition, LGBT communities, liberals, the Left and cultural elites played the role of dark characters on state-owned television. On the other hand, Jarosław Kaczyński, the leader of the Law and Justice party, played the role of the almighty ‘father of the nation’ and was the source of truth and the author of the main message in the news programme. It was he who enhanced the ideological message of television, and his statements constituted the main and final arguments in political assessments presented in the news programmes.